Acral Lentiginous Melanoma: Do Surgical Approach and Sentinel Lymph Node Biopsy Matter?. Issue 3 (23rd March 2020) - Walker, Marc E.; Han, Gang; Gabrick, Kyle; Kanouzi, Jack; Lo, Ying-Chun; Galan, Anjela; Clune, James; Narayan, Deepak; Ariyan, Stephan; Han, Dale
Abstract : Background: Management of acral lentiginous melanoma (ALM) remains controversial. Traditionally, ALM was managed with digit amputation (DA), resulting in significant morbidity, but recent evidence has advocated for digit sparing management. Furthermore, the significance of nodal metastasis for ALM is not well reported. The aims of this study were to determine if surgical approach for primary ALM impacts outcomes and to evaluate the predictive value of nodal status for ALM. Methods: Patients with localized ALM diagnosed from 1982 to 2017 were retrospectively identified. Clinicopathologic characteristics were correlated with surgical approach, nodal metastasis, overall survival, and recurrence-free survival. Results: There were 47 patients with ALM. Median age was 59 years, and median thickness was 3 mm. 51% of patients underwent wide local excision (WLE), 27.9% underwent DA, and 20.9% underwent partial digit amputation (PDA). ALM on the hand versus foot (OR: 12.7, 95%, confidence interval (CI), 2.0–80.1; P = 0.007) and subungual versus nonsubungual location (OR: 28.0, 95% confidence interval, 2.7–295.7; P = 0.006) were significantly associated with surgical approach (DA and PDA versus WLE). There were no significant differences in overall survival or recurrence-free survival between DA, PDA, or WLE cases ( P = 0.481 and P = 0.778, respectively). There were no significant differences in overall survival or recurrence-free survival based on nodal status ( P = 0.562 and P = 0.136, respectively). Conclusions: No significant differences in overall survival or recurrence-free survival were seen between ALM patients treated with DA, PDA, and WLE. Given these results, PDA or WLE may be options in select patients with digital ALM; however, careful consideration must be taken when deciding on the surgical approach.